Applying experiences with declarative codifications of software architectures on cod - Wuyts, Roel
This position paper presents some preliminary work we made for applying declaractive component oriented design in the context of embedded devices. We quickly describes COMES the model we develop and present how logic rules can be used to describe architectures.